PENGARUH HARGA, CITRA MEREK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA VIOLET BAKERY KOTA PROBOLINGGO - Abir Afifah; Ngatimun Ngatimun; Yayuk Indah Wahyuning Tyas (Politeknik Negeri Jakarta, 2025)
The increasingly rapid and unlimited development of the era makes human desires and needs increasingly numerous. Currently, humans are no longer able to fulfill their own desires and needs, so that a form is expected that can provide this. This study aims to identify what factors make consumers make purchasing decisions. This is whether influenced by several factors such as price, brand image, or location. This study uses an associative quantitative method with a sampling technique using an incidental technique, and data acquisition is carried out by distributing questionnaires to consumers at Violet Bakery, Probolinggo City. Testing in this study using the SPSS23 test. The results indicate that price, brand image, and location have a positive and significant effect on purchasing decisions at Violet Bakery, Probolinggo City. Keywords: price, brand image, location, and purchasing decisions.